The fundamental theorem of algebra says this cubic has three roots, so we could write it as
![4x^3+32x^2+79x+60=4(x-a)(x-b)(x-c)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t9tf63i1jbo7aybs0lvalpxxtlewc93qj4.png)
We're told one of the roots is equal to the sum of the other two, so we could take
:
![4x^3+32x^2+79x+60=4(x-a)(x-b)(x-a-b)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zk29c2ntnarxt8fobwo39o15ox0s8amyei.png)
If we expand the right side, we get
![4\bigg(x^3-2(a+b)x^2+(a^2+3ab+b^2)x-(a^2b+ab^2)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f5tscdj68tlj4yili4y1r2ie1w0u00pazg.png)
For two polynomial to be equal, the coefficients of terms of the same degree must match, so that
![\begin{cases}4=4&(x^3)\\32=-8(a+b)&(x^2)\\79=4(a^2+3ab+b^2)&(x)\\60=-4(a^2b+ab^2)&\text{(constant)}\end{cases}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e1shsba1zkz40wg32e0h3nquen0z5zazf3.png)
Now we can find
.
![32=-8(a+b)=-8c\implies c=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qhyns71593x7llnp7lqurjflg8j8v1js35.png)
This tells us that
is a factor, so dividing the original cubic by this returns a remainder of 0.
![(4x^3+32x^2+79x+60)/(x+4)=4x^2+16x+15=4\left(x+\frac32\right)\left(x+\frac52\right)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nsamfy1xjh1tx0mx9iyy6k6obi8zdzufoz.png)
which further tells us that
and
.